The Hijāb Verse between the Ordinary Ruling and the Discourse Evidence: A Jurisprudential Study in the Māliki School - Al-Ghafod , Mohamad Salim ALI (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: The study aims to review some of the doubts raised concerning the verse of the (Hijāb) by the proponents of the modern interpretation of religious discourse, which is in their claim that: the (Hijāb) is only obligatory for the Prophet’s wives and the women of their time. and it was obligatory due to circumstances prevailing at that time, but now the ruling no longer applies. Methods: The study used descriptive methods to provide an accurate description of the issue, an analytical method to scrutinize Hijāb verse doubts, and a deductive method to derive jurisprudential conclusions about their validity. Results: The study concluded that these doubts do not align with the foundational principles. The Hijāb is not merely a historical mandate limited to the time of revelation. Building a ruling based on the condition mentioned in the verse and considering that it has a reverse meaning (mafhōm) is not valid. The condition in the verse serves a rhetorical purpose, and we do not negate a clear literal meaning (mantōq) with a reverse meaning (mafhōm). Conclusion: Not requiring intention for wearing the Hijāb does not make it a customary practice; it remains an act of worship rooted in revelation, not tradition or history. The condition of obligatory Hijāb-wearing in the verse holds has no reverse meaning (mafhōm), and thus these doubts do not withstand scrutiny within the framework of foundational jurisprudence.